Diseño de un proceso para la obtención de etanol a partir de la cáscara de arroz. - Pérez Molleda, María Rebeca (2013)
The production of ethanol for the energy market has traditionally been from corn and sugar cane biomass. The use of such biomass as energy feedstocks has recently been criticised as ill-fated due to competitive threat against food supplies. At the same time, ethanol production from cellulosic biomass is becoming increasingly popular. In this paper, we analyse rice husk (RH) as a cellulosic feedstock for ethanol biofuel production on the ground of its abundance. The global potential production of bioethanol from RH is estimated herein and found to be in the order of 2.9 to 24.3 GL per annum, potentially satisfying around one fifth of the global ethanol biofuel demand for E10 a 10% gasohol fuel blend. Furthermore, we show that this is especially advantageous for places where there is plenty of rice husk and where economic growth and energy demand have soared.